“Made In China” Products and the Implication of Ethnic Identification Strength - Huat Wei Huang; Ernest Cyril de Run; Hiram Ting; Huong Sung Colin Ting (International Review of Management and Marketing, 2016)
This paper seeks to examine the effect of ethnic identification strength between the Malays and Chinese towards purchasing “Made in China” products. A quantitative approach by means of self-administered questionnaire was adopted. 252 Malay and 251 Chinese respondents’ data were collected from local institutions of higher learning. Independent Sample t-tests and Multiple Regression Analysis were used to look into difference and relationship pertaining to Country of Origin (COO) image, product knowledge, product involvement, information search and purchase intention. The findings show Malays and Chinese are different in terms of their perceptions towards COO image and product involvement. Moreover, COO image is found to be significantly different among Malays and Chinese with strong and weak ethnic identification. However, COO image is found to have no effect on information search and purchase intention although both ethnic groups are generally in favour of products “Made in China”. Instead product knowledge and involvement are found to be essential. This study suggests that marketers and managers need to understand what is shared and what is not among Malays and Chinese in a developing and diverse society like Malaysia. Despite the effect of COO image and ethnic identification strength, product knowledge and involvement play pivotal role in understanding consumers today.